2002
DOI: 10.1103/physrevlett.88.047005
|View full text |Cite
|
Sign up to set email alerts
|

Microwave Conductivity and Penetration Depth in the Heavy Fermion SuperconductorCeCoIn5

Abstract: The electrodynamic properties of the quasi-two-dimensional heavy fermion superconductor CeCoIn5 have been investigated by microwave surface impedance measurements over a wide range of microwave frequencies and temperatures. We derive a value penetration depth lambda(0) approximately 190 nm, with a strong linear term in the temperature dependence of lambda(T) below T(c)/3, consistent with a superconducting gap with line nodes. The real part of the conductivity displays a broad peak at low temperatures consisten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
67
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(77 citation statements)
references
References 18 publications
(24 reference statements)
9
67
1
Order By: Relevance
“…We see that the frequency dependence of 1/d 2 is indeed very strong and note the difficulty of isolating 1=l 2 L ðTÞ from a measurement at any single microwave frequency. 1=l 2 L ðTÞ has a strong temperature dependence across the whole temperature range, in contrast to an s-wave superconductor 15 , but is not strictly linear at low temperatures, as reported in previous studies [17][18][19] . This can be seen clearly in Fig.…”
Section: Resultsmentioning
confidence: 72%
See 2 more Smart Citations
“…We see that the frequency dependence of 1/d 2 is indeed very strong and note the difficulty of isolating 1=l 2 L ðTÞ from a measurement at any single microwave frequency. 1=l 2 L ðTÞ has a strong temperature dependence across the whole temperature range, in contrast to an s-wave superconductor 15 , but is not strictly linear at low temperatures, as reported in previous studies [17][18][19] . This can be seen clearly in Fig.…”
Section: Resultsmentioning
confidence: 72%
“…In the cuprates, where similarly strong scattering is observed in the normal state 27 , electrodynamic measurements show a rapid collapse in quasiparticle scattering on cooling through T c [28][29][30] , indicating that the charge carriers couple to a spectrum of fluctuations of electronic origin, in contrast to the phonons of a conventional metal. Early measurements on CeCoIn 5 are suggestive of similar behaviour 2,17 .…”
mentioning
confidence: 86%
See 1 more Smart Citation
“…The competition between increasing τ and decreasing quasiparticle density n n (T ) = n − n s (T ) makes a peak in σ 1 (T ). This behavior is ubiquitous among superconductors having strong inelastic scattering in the normal state [27,44,74]. Following the pioneering work by Bonn et al [45], we employ the two-fluid analysis to extract the quasiparticle scattering rate 1/τ (T ) at low temperatures below ∼ 25 K. In Fig.…”
Section: Quasiparticle Conductivitymentioning
confidence: 99%
“…In particular, CeCoIn 5 continues to generate great interest, as it exhibits strong Pauli paramagnetic effects [139] that, combined with its quasi-2D structure and super-clean crystal properties [140,141], fulfill the stringent requirements for the stabilization of the inhomogeneous Fulde-Ferrell-Larkin-Ovchinnikov (FFLO) state [142,143]. However, up to now, unambiguous microscopic proof for the existence of the FFLO state does not exist, in spite of the multitude of experimental signatures that were reported that suggest the formation of a FFLO phase [144][145][146][147][148].…”
Section: Cein 3 and Cemin (M = Co Ir Rh)mentioning
confidence: 99%